Evaluation of national athletes’ attitude to vitamin/mineral supplements - حمید محبی; ابوذر جوربنیان; سعید یونسی; رضا معصومی راد (فیزیولوژی ورزش و فعالیت بدنی, 2009)
Purpose: The aim of this study was to investigate the nutrition-related knowledge, attitude andvitamin/mineral supplements intake of elite national athletes. Methods: Sixty eight IranianNational Athletes from volleyball (n=9), karate (n=12), weightlifting (n=7), wresting (n=7),taekwondo (n=10), basketball (n=10), boxing (n=8), and Judo (n=5) were included in this study.The self-administered questionnaire examined the athlete’s nutrition knowledge, attitude andsupplement frequency intake. The athlete’s height, weight, and sport experience were recorded.Results: High mean dietary intake scores were found for vitamin E, calcium, multivitamin and lowmean dietary intake scores were found for folate and pantothenic acid. A moderate correlation wasfound between attitude and supplements intake (r=0.545, P<0.01). There were significantdifferences in the amount of vitamin and mineral supplements intake between weight lifting elitenational athletes team compared to others (P<0.05). Moreover, the result showed significantdifferences between elite national athletes of boxing team compared to volleyball, taekwondo, andbasketball teams (P<0.05). Conclusions: It can be concluded that athletes in national teams shouldextend their knowledge regarding to the amount of vitamin and mineral supplements intake. Futureresearch also, should explore factors other than knowledge and attitude which may have influenceon dietary intake among national athletes.